Exploring the relationship between supervisory support, self-efficacy, and satisfaction among nursing students in Saudi Arabia - Thurayya Eid; Faihan F. Alshaibany; Abdulaziz M. Alodhailah; Waleed M. Alshehri (PLoS ONE, 2026)
Background Supervisory support during clinical placements is central to nursing students’ professional development. Professional self-efficacy, students’ confidence in performing clinical tasks, is increasingly recognised as a key outcome associated with transition to practice and workforce retention. In Saudi Arabia, Vision 2030 healthcare reforms have intensified demand for qualified nurses, making the quality of clinical supervision a strategic priority. This study examined the relationships among supervisory support, professional self-efficacy, and nursing student satisfaction at King Saud University-affiliated hospitals. Methods This descriptive cross-sectional study was conducted among 145 nursing students (second-, third-, and fourth-year bachelor’s degree students) at three King Saud University-affiliated teaching hospitals in Riyadh, Saudi Arabia. Participants were selected using stratified random sampling based on year of study. Data were collected using four validated instruments: a sociodemographic questionnaire, the Supervisory Support Scale (9 items; Cronbach’s α = 0.90), the Nursing Student Satisfaction Scale (6 items; α = 0.88), and an adapted Professional Self-Efficacy Scale (12 items; α = 0.90). Descriptive statistics summarised the three key study variables (supervisory support, professional self-efficacy, and student satisfaction) alongside sociodemographic characteristics. Pearson correlation coefficients assessed the strength and direction of linear associations among continuous study variables. Formal mediation analysis was conducted using the PROCESS macro (Model 4) with 5,000 bias-corrected bootstrap resampling iterations. Results Of 175 students approached and meeting eligibility criteria, 145 returned valid questionnaires (response rate = 82.9%). The sample was predominantly female (60.7%) and in the age range of 20–22 years (66.9%). Students reported high levels of supervisory support (mean = 4.10 ± 0.53 out of 5), satisfaction with clinical placements (mean = 4.11 ± 0.52), and professional self-efficacy (mean = 4.06 ± 0.56). Supervisory support was strongly correlated with satisfaction (r = 0.68, p < 0.001) and professional self-efficacy (r = 0.57, p < 0.001); professional self-efficacy was positively correlated with satisfaction (r = 0.49, p < 0.001Statistical mediation analysis revealed that professional self-efficacy partially mediated the supervisory support–satisfaction relationship: the indirect association (ab = 0.13, 95% CI [0.07, 0.19]) was statistically significant and accounted for approximately 19% of the total association. In regression analysis, supervisory support remained significantly associated with satisfaction (β = 0.43, p < 0.001) even after accounting for professional self-efficacy, consistent with partial statistical mediation. Conclusions Supervisory support was significantly and positively associated with nursing students’ satisfaction and professional self-efficacy. These findings, grounded in social cognitive theory, suggest that high-quality supervision may enhance clinical learning outcomes both directly and through strengthening students’ professional confidence. Standardising supervisory practices, investing in supervisor training, and creating structured feedback mechanisms are priorities for improving nursing education in Saudi Arabia and advancing national nursing workforce goals under Vision 2030.